Transformación de residuos de gallinaza para su aprovechamiento como materia prima (2023)
Chicken manure is considered one of the biggest problems for the environment from the poultry production sector due to the large amount of pollutants it generates; For this reason, it is important to highlight that this organic waste can be an opportunity to be transformed into a new product, which can be given a greater added value and, thus, by using the waste generated in the sheds that new benefit. brings new possibilities to improve the environment.